Chromosome engineering in plants. - Gupta, P. K., 1936-; Tsuchiya, T. (Takumi), 1923- (Developments in plant genetics and breeding., 1991)
This two-volume work surveys the entire range of general aspects of chromosome research in plants. The first volume covers cytogenetics of cereals and millets with more than one chapter being devoted to the same crop to give a detailed treatment to an up-to-date status of chromosome research. This second volume deals with cytogenetics of plant materials including legumes, vegetable and oil crops, sugar crops, forage crops: fibre crops, medicinal crops and ornamentals. The book will be useful both as a reference work and a teaching aid to satisfy a wide range of workers. Every chapter has been written by an expert who has been involved in chromosome research on a particular plant material for many years so that the treatment is authoritative and up-to-date in most cases.